THE INFLUENCE OF PHYSICAL WORK ENVIRONMENT FACTORS ON THE PERFORMANCE OF EMPLOYEES OF THE MOJOKERTO REGENCY HEALTH OFFICE - Abidin, Feri Muhammad; Diana, Sulis; Eka Dyah Katiningrum (Departement Research and Community Engagement Bina Sehat PPNI Institute of Health Science, Indonesia, 2025)
Efforts to create a good and comfortable physical work environment must be made by agencies in order to support the achievement of high performance for employees. The purpose of this study was to analyze the influence of physical environmental factors on the performance of employees of the Mojokerto District Health Office. This study was conducted with a cross sectional approach with a sample of 76 employees selected by simple random sampling technique. data were collected with a room thermometer, sound level meter, luxmeter and comfort measurement questionnaire. The data were then analyzed using logistic regression test. The results showed that almost all of the furniture used by employees to work was comfortable (79.5%), most of the rooms had more than average noise levels (59.1%), all rooms had room temperature (15-30o Celsius) (100%), almost all rooms had inappropriate lighting (88.6%). The results of the logistic regression test explain that the comfort of office furniture has no effect on employee performance (p value = 0.545), the noise level has no effect on employee performance (pvalue = 0.739). employee workplace air temperature has no effect on employee performance (pvalue = 0.087). Workplace lighting levels affect employee performance. (p value = 0.026) Together there is an influence of all physical environmental factors on employee performance and there is no most dominant factor in influencing the performance of employees of the Mojokerto District Health Office (pvalue = 0.000). Sufficient lighting does not interfere with employee concentration so that they can work well and focus and have good performance. Therefore, the Health Office should begin to rehabilitate the facilities owned so as to create a conducive work environment for employees.